2020
DOI: 10.26452/ijrps.v11i4.3948
|View full text |Cite
|
Sign up to set email alerts
|

In Silico studies of 4-Anilino Quinazoline derivatives as Anti-tubercular Agents

Abstract: Inh A, the Enoyl Acyl Carrier protein Reductase from Mycobacterium tuberculosis is one of the pivotal enzyme involved in the mycobacterial fatty acid elongation cycle and has been considered as an important target for anti-tubercular screening. Inhibition of Inh A affects the biosynthesis of the mycolic acids, which are the central constituents of the mycobacterial cell wall. In the present research work, 4-anilino quinazoline derivatives were designed based on the quinazoline based drugs by means of lipophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…and Dunaliella sp . (0.34 mg GAE/g and 0.17 mg GAE/g, respectively) [11] . This discrepancy may be attributed to the choice of extraction solvent, as the ethanol‐water cosolvent (7 : 3, v / v ) employed has been demonstrated to be superior in terms of solvent efficiency and component fractionation when compared to hexane, pure ethanol, methanol and water [12] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and Dunaliella sp . (0.34 mg GAE/g and 0.17 mg GAE/g, respectively) [11] . This discrepancy may be attributed to the choice of extraction solvent, as the ethanol‐water cosolvent (7 : 3, v / v ) employed has been demonstrated to be superior in terms of solvent efficiency and component fractionation when compared to hexane, pure ethanol, methanol and water [12] .…”
Section: Resultsmentioning
confidence: 99%
“…(0.34 mg GAE/g and 0.17 mg GAE/g, respectively). [11] This discrepancy may be attributed to the choice of extraction solvent, as the ethanol-water cosolvent (7 : 3, v/v) employed has been demonstrated to be superior in terms of solvent efficiency and component fractionation when compared to hexane, pure ethanol, methanol and water. [12] Additionally, environment factors, such as geographic location and climate conditions, [13] can influence the production of phytochemicals, including phenolic compounds.…”
Section: Phenolic Estimationmentioning
confidence: 99%
“…Additionally, unlike our study showing antioxidant activity of different algal compounds, other published studies have only evaluated the total antioxidant activity. The highest total antioxidant activities measured in microalgae are for the marine diatom Navicula clavata and the green microalgae Chlorella marina and Dunaliella salina, which have shown total antioxidant activity of ~0.6, 1.0, and 0.9 mg EAA g -1 dry weight, respectively (Hemalatha et al, 2013). A study by Haoujar et al, 2022 showed total antioxidant capacity of ~0.40 mg EAA g -1 dry weight for the green microalgae Nannochloropsis gaditana and Tetraselmis suecica and for the marine diatom Phaeodactylum tricornutum.…”
Section: Discussionmentioning
confidence: 99%
“…Найголовнішою особливістю хімічного складу морських водоростей є вміст йоду (Teas et al,2004) як важливого мікроелемента, необхідного для синтезу гормонів щитоподібної залози, тироксину і трийодтироніну. Гормони щитоподібної залози регулюють широкий спектр клітинних і фізіологічних функцій, таких як нормальний ріст і розвиток, нервова диференціація і регуляція метаболізму (Parthiban et al, 2013).…”
unclassified